Keterampilan Komunikasi Interpersonal Mahasiswa Bimbingan dan Konseling Pendidikan Islam yang Tinggal di Pesantren : Sebuah Studi Deskriptif - Yanawati, Riska; Rahmansyah, Faisal Akbar; Mariyam, Ade Siti (Universitas Negeri Makassar, 2025)
This study aims to obtain a general overview of the interpersonal communication skills of Islamic Guidance and Counseling students at KH. Ruhiat Cipasung Tasikmalaya Islamic University who live in Islamic boarding schools. Interpersonal communication is crucial for social cohesion and self-development in the Islamic boarding school environment. This study used a quantitative approach with descriptive methods, involving 117 students living in the Islamic boarding school. Data were collected using an interpersonal communication skills instrument (DeVito, 2016) and analyzed statistically. The results showed that the interpersonal communication skills of students living in the Islamic boarding school tended to be moderate (mean 0.71; SD 0.33). A total of 70% (82 students) were in the moderate category, 18% (21 students) were high, and 12% (14 students) were low. These findings indicate that BKPI students living in Islamic boarding schools have adequate communication skills, but need to improve their empathy and active listening. The hierarchical and ethical environment of Islamic boarding schools can influence communication patterns. Students with low skills require special attention. The interpersonal communication skills of Islamic boarding school students are mostly moderate and require development. The implication of this research is the importance of strengthening the interpersonal communication program within the BKPI curriculum.